2022
DOI: 10.1007/s11904-022-00615-z
|View full text |Cite
|
Sign up to set email alerts
|

Applying Behavioural Insights to HIV Prevention and Management: a Scoping Review

Abstract: Purpose of Review This scoping review summarises the literature on HIV prevention and management interventions utilizing behavioural economic principles encapsulated in the MINDSPACE framework. Recent Findings MINDSPACE is an acronym developed by the UK’s behavioural insights team to summarise nine key influences on human behaviour: Messenger, Incentives, Norms, Default, Salience, Priming, Affect, Commitment, and Ego. These effects have been used in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…Because of limited resources and lack of sustainability, financial nudges are viewed as either not feasible, difficult to scale, or outside the range of program options by policy makers and program managers, the primary audience for this scoping review. Therefore financial nudges were excluded from this scoping review, but they are included in Andrawis et al 62…”
Section: Resultsmentioning
confidence: 99%
“…Because of limited resources and lack of sustainability, financial nudges are viewed as either not feasible, difficult to scale, or outside the range of program options by policy makers and program managers, the primary audience for this scoping review. Therefore financial nudges were excluded from this scoping review, but they are included in Andrawis et al 62…”
Section: Resultsmentioning
confidence: 99%
“…In-building intuitive information feedbacks and framing nudges within the person–caregiver interaction process, to reinforce person's perceptions on improvement of their physical health—however trivial—could unease treatment fatigue. 33 , 34 , 35 , 36 , 37 , 38 Gain framing approaches for developing communication messages for PwDR-TB could be a useful way forward. 39 Caregivers could positively reinforce the incremental milestones which persons have achieved through the treatment (e.g., increasing probability of cure, decreasing transmission risk for family members) to help ease their perception burden.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the authors concluded that compared to standard profit-based incentives, offering lottery incentives and losses framed incentives did not lead to a significant increase in HIV testing. However, when low-cost incentives are offered to promote HIV testing, designing lottery prizes may be a better approach than profit-based incentives [ 85 ]. Nudges can also have adverse consequences.…”
Section: Discussionmentioning
confidence: 99%